Investigating students' acceptance of E-learning system in Higher Educational Environments in the UAE: Applying the Extended Technology Acceptance Model (TAM) - SALLOUM, SAID ABDELRAHIM SAID (2018)
DISSERTATION WITH DISTINCTION